Efficiency of local government expenditure in health sector - Sylviana, Widya; Suyanto, Suyanto (Nur Science Institute, 2024)
This study evaluates the efficiency of local government expenditures in the health sector, crucial for growth and productivity. Using Data Envelopment Analysis, it examines pre- and post-decentralization periods. Before decentralization, only Makassar (Sulawesi) and Gianyar (Bali and Nusa Tenggara) achieved full efficiency. Post-decentralization, Bengkalis, Kota Pematang Siantar, and Simalungun (Sumatera) reached efficiency. Findings reveal that Papua’s regions have the lowest efficiency scores, while Sulawesi’s are the highest. Papua averages 0.80, below the national average of 0.90, whereas Sulawesi scores 0.93. Overall, efficiency improved post-decentralization. The study highlights the need for government efforts to enhance health expenditure efficiency both before and after fiscal decentralization to achieve optimal results.